(untitled) (Journal of Sciences & Technology, 2018)
A boundary layer separation on a NACA0012 airfoil at a low Reynolds number is numerically investigated. The governing equations are discretized with the finite volume method. The boundary layer separation is examined through the flow structure. Beyond an angle of attack of 8°, a small separation region is detected near the trailing-edge of the airfoil. As the angle of attack increases, the separation region grows up and moves towards the leading edge. In order to control the separation, a parabolic distribution blowing is applied along the separated region. The effectiveness of the control is shown, leading to the improvement of the lift and the lift to drag ratio. As the blowing jet velocity is increased the size of the separation bubble decreases until it disappears.